21st century skills and digital skills, are one and the same thing? - Belchior-Rocha, H.; Mauritti, R.; Monteiro, J.; Carneiro, L. (EDULEARN20 Proceedings, 2020)
The preparation of students of new generations for the labour market and for new social contexts currently requires higher education (ES) to reflect and reorganize its learning and training offer. In this sense, higher education institutions (HEIs) need to pursue a set of challenges, which include identifying and understanding the characteristics and needs of new students generations. Over the last decade's reference models on transversal competences (soft skills) have been established, classifying them on several nomenclatures as instrumental, interpersonal and systemic, but not always considering the temporal, and social, economic context of these same references. With the aim of designing an adequate formative offer, we have developed a study based on the systematization of the literature on the extent of reference models, categorization and terminology of references, regarding competences skills and aptitudes, and reflect, if in some cases, we are talking about equal, different or complementary competences, in one single one. An asymmetry still seems evident between the needs for skills of a digitalized society and the development by HEIs of an educational offer convergent with these same needs, not only at the professional level but also of behavioural, emotional, social, cultural capacities. Moreover, unlike digital skills, 21st-century skills are not necessarily underpinned by digital technologies. If two decades ago the categorization terminology was limited to instrumental, interpersonal and systemic skills, the research in this area develops more detailed frameworks that do not separate 21st-century skills from digital skills, structuring this large set into foundation or fundamental, social and emotional skills to learn, create and innovate, emancipatory and humanistic and artistic skills. In addition, the discussion focuses on the ability of students to acquire and develop these new skills in an academic and professional context, leaving aside the ability of teachers to conduct and integrate those skills in a transversal and transdisciplinary in teaching and learning approaches.